Bazilijonų, misionierių ir pijorų knygų rinkiniai Lietuvoje 1800–1839 m.: istorinės rekonstrukcijos bandymas - Pacevičius, Arvydas (Knygotyra, 1995)
In the former territory of the Great Duchy of Lithuania, which was incorporated into the Russian Empire in 1795, the Catholic and Unit (the Basilians) cloisters had numerous and valuable book collections. Such issues as the organization and functioning of the libraries, the structure of the funds, even the number of books were not studied enough yet.The analysis of inventories and catalogues of the cloisters libraries confirms the supposition that the quantity and character of books collections depended on different internal (the regulations of monastic orders, the character of institutions) and external (the programs of fundators, the book market, the politics of the tsarist regime) circumstances.The largest monastic libraries were concentrated in Vilnius. The historical sources testify, that there were 4120 vol. of books in the library of the Missionaries in Vilnius in 1804 (and 7210 vol. in 1830), 4014 vol. in the library of the Piarists in 1804 (4524 vol in 1830), 6694 vol. in the library of the Basilians in 1823 (6123 vol. in 1837).The arrangement of the libraries funds was various especially in field of classification of books. Gradually the civil law and history were separated from canon law and Church history, new sections, such us “Mathematics and Astronomy”, “Geography”, “Economy” appeared. The cloisters intended some fixed sums of money for purchase of new books, about 50 silver roubles a year for this aim.The catalogue of the Basilian library in Vilnius exposes the large number of books in German (especially in sections of “Ascetica”, “History”) also in French (the majority of books were in Latin and Polish). The incunabula which is not recorded in the national bibliography was in this library too. In 1837 bookstore of the Basilians printing-house in Vilnius had a numerous collection of the Lithuanian books (about 3000 vol.), which were printed there.When the monastic libraries (since 1832) were gradually liquidated, the large number of books got into the private collections of M. Herburt, A. Moszynski, Erdmann.Even the preliminary information allows us to conclude, that the libraries of the Basilians, the Piarists and the Missionaries were among the largest and the best completed monastic libraries in the first half of the 19th century. Through the educational institutions they also satisfied the intellectual needs of the society.